Astrometric Study of Galactic Clusters. I. NGC 3532 - Suhardja Wiramihardja; Yayan Sugianto; Muhammad Ikbal Arifyanto (Institut Teknologi Bandung, 2008)
Astrometric study of galactic clusters using UCAC2 catalog containing proper motion data is described. Kinematicalanalysis is applied to determine cluster membership. The near infrared photometric data of the same catalog is used toderive physical parameters of the cluster. In the present study the case for NGC 3532 is given. An isochrones fitting tothe color-magnitude diagram gives the age of cluster in log t = 8.85 and the distance of 515 Â± 41 pc with infraredreddening in J filter of 0.043 Â± 0.017 mag. Our results are in good agreement with results of previous studies.